IMPROVEMENT OF ECONOMIC MECHANISMS OF FUNCTIONING OF THE ELECTRIC POWER INDUSTRY OF UZBEKISTAN - Tursunov Alisher Mukhamadnazirovich (Ecominds Press, 2025)
The article evaluates the state of economic mechanisms such as state regulation, tariff policy, investment in infrastructure, stimulation of energy efficiency and ensuring energy security in the process of functioning of the electric power industry of Uzbekistan, identifies the main problems and proposes ways of their solution aimed at ensuring sustainable development of the energy industry.
Keywords: Economic mechanisms, electric power industry, Uzbekistan, regulatory system, tariff policy, investment, renewable energy sources, energy efficiency.